O sistema mágico: a imprensa e os valores femininos presentes no cinema (1938-1941) - Gama, Rafael da (2014)
This research analyzes how part of the press of Belém, during the late 1930s and the early 1940s (1938-1941), portrays the cinema and the woman. We will seek to debate in what manner the press built female ideals associated to the movies, through issues, illustrations and advertisements. The major documentary sources that will be analyzed are two variety magazines "A Semana" and "Pará Ilustrado", that used to circulate in the city which constantly issued the State of Pará, promoting spaces, ideals and social behaviors. We will also examine the great press of Pará, the newspaper "Folha do Norte" and the female catholic magazine "Quero", discussing on how these media press depicted the city of Belém, its movie theaters and content. Furthermore, we will apprehend the approach made by the press towards women, the feminine ideal which they presented and how they used to articulate it in the direction of the female value shown in the cinema. Thus, the press will be discussed as an active agent in the urban medium, used by social groups for diffusion of spaces, behaviors and values, in this case, more specifically, in the propagation and consolidation of the cinema in the city, whether articulating with its social construction of the city of Belém or making a strong use of the feminine in the direction of disclosure and appreciation of the cinema